2022
DOI: 10.3390/rs14030762
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Forest Mapping in China Using the Dense Landsat 8 Image Archive and Google Earth Engine

Abstract: It is of great significance to understand the extent and distribution of bamboo for its valuable ecological services and economic benefits. However, it is challenging to map bamboo using remote sensing images over a large area because of the similarity between bamboo and other vegetation types, the availability of clear optical images, huge workload of image processing, and sample collection. In this study, we use the Landsat 8 times series images archive to map bamboo forests in China via the Google Earth eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Therefore, combining multiple feature variables helped to improve the classification accuracy, which can also be proved from previous studies. For example, Qi et al [ 54 ] found that NDVI, NDMI, and texture features make bamboo forest classification more accurate and reliable. Li et al [ 53 ] combined spectral bands, vegetation indices, texture, and topographic features to map the distribution of bamboo forests in Zhejiang from 1990 to 2014, and the OA was above 85%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, combining multiple feature variables helped to improve the classification accuracy, which can also be proved from previous studies. For example, Qi et al [ 54 ] found that NDVI, NDMI, and texture features make bamboo forest classification more accurate and reliable. Li et al [ 53 ] combined spectral bands, vegetation indices, texture, and topographic features to map the distribution of bamboo forests in Zhejiang from 1990 to 2014, and the OA was above 85%.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with similar studies, the UA of Phyllostachys edulis was 4.5–14.5% higher than that of SVM [ 67 , 69 ]. The highest UA of bamboo forest is about 7.0% and 15.5% higher than that of decision tree and random forest, respectively [ 54 , 99 ]. The OA of bamboo forest is comparable to that of the artificial neural network, but the UA is higher than that of the artificial neural network [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MODIS images were used to constitute a MODIS dataset with four time (2005, 2010, 2015, 2020), spatial resolution of 500 m, and three products (MOD091, MOD11A2, MOD13A1) in the GEE platform [27], and the GEE platform was used to calculate the RSEIs of the study area for 2005, 2010, 2015, and 2020 RSEI.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, Landsat 8 satellite image data can completely overcome the limitations of traditional methods in monitoring and evaluating drought [12]. It can provide a synoptic and comprehensive view of the area, allowing for the detection of changes in vegetation health, land surface temperature, and precipitation patterns [13]. Additionally, Landsat 8 satellite image data can be collected regularly which enables the monitoring of drought over time and the assessment of its impacts on vegetation and the environment [14].…”
Section: Introductionmentioning
confidence: 99%